“They went out from us, but they did not belong to us”. On the history of renegading of the former theologian Alexander Osipov - Alexander Prilutskii; Sergey Firsov (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2024)
The publication is dedicated to the reaction of the student of the Leningrad Theological Seminary, priest Vasily Zavodchikov (1924–2008) to the renunciation of religion and the Church, announced in December 1959, the Orthodox theologian, former professor of the Leningrad theological schools and former archpriest Alexander Alexandrovich Osipov (1911–1967). In December 1959, priest Vasily Zavodchikov wrote and sent an «Open Letter» to A. A. Osipov, in which he tried to explain that Osipov’s public departure from the Church was not only a betrayal of Orthodoxy, but also his deep moral error. The letter, emotional in form and not entirely literary, should be considered as an important historical and socio-psychological document that allows us to better understand the era of the «Khrushchev Thaw”, which became a time of new persecution for the Church. In addition, this publication presents materials regarding the renegadeness of A. A. Osipov, compiled by Father Vasily in 1999, and now also a historical document that allows us to evaluate the psychology of perception of what happened in 1959 by a clergyman who survived the times of the atheism and assessed Soviet atheism from the point of view of new, «post-Soviet» realities.